Experimental investigation for metal-filling system of pressure diecasting process on a cold chamber machine - Sulaiman, S.; Hamouda, A.M.S.; Gethin, D.T. (Elsevier, 2001)
This paper describes the molten metal flow in the filling system of pressure diecasting process. An experiment was carried out directly on a pressure diecasting machine (or cold chamber machine) to obtain the flow characteristics and pressure history. Three types of experiments were carried out on the machine, i.e. runs under normal pressure diecasting conditions, runs using a dry shot where no metal was injected, and tests using a short shot where piston plunger movement was stopped prior to complete fill of the cavity. Several shots were recorded and pressure time history and displacement time history under normal casting condition for the metal-injection phase were investigated and carried out successfully. The results are presented in a format, which enable convenient comparison with the predicted data.